Body and Soul - Bron, Matthieu (France; Mozambique, 2010)
The film follows Victoria, Vasco and Mariana, three young Mozambicans, facing their handicap with an impressive strength. Victoria organises a fashion show with disabled women to make them confident again in their femininity and charm. Mariana has an incredible social energy and breaks the prejudices and psychological barriers of an ever-growing circle of friends. Vasco overcomes all the difficulties to go to work including the refusal of many bus drivers to take wheelchairs. Every day, they disarm the people’s prejudices with their extraordinary personalities.
Verzio Film Festival Submission
Keywords: Documentary films